Developing a competency scale for selecting and assessing psychological peer counselors in ethnic-area colleges: a pilot study in Guizhou Province, China - Guo, Junru; Chen, Wei; Liu, Meilan; Jiang, Lirong; Chen, Yurong; Zhao, Xiaoqing; Peng, Dan; Jiang, Xuefeng; Wang, Li; Wang, Dongmei (Frontiers in Psychology, 2024)
IntroductionPsychological peer counselors play a crucial role in the mental health education of college students, especially in ethnic regions. The study zeroes in on developing a tool for selecting and assessing psychological peer counselors in ethnic-area colleges and universities, using Guizhou Province as a case study.Materials and methodsFocusing on psychological peer counselors in ethnic-area higher education institutions, this study amalgamates open-ended questionnaire surveys, interviews, and literature analysis to construct a competency characteristics questionnaire. The questionnaire underwent pretesting with 450 psychological peer counselors in colleges and universities, involving entry analysis and exploratory factor analysis. Subsequently, it was administered formally to 570 psychological peer counselors for confirmatory factor analysis, coupled with internal consistency reliability tests at the empirical validity level. A subset of 230 psychological peer counselors was retested after three-month intervals. The Interpersonal Reaction Coefficient Scale (IRC-C) and the General Self-Efficacy Scale (GSES) were employed for validity tests.ResultsThe questionnaire consists of 21 items across four factors—role identity, communication sensitivity, personal traits, and professional ethic—cumulatively explaining 66.26% of the variance. The validated factor analyses demonstrated a good model fit (X2/df = 2.67, SRMR = 0.04, TLI/NNFI = 0.93, CFI = 0.94, RMSEA = 0.05, AIC = 21960.17, BIC = 22261.10). The questionnaire’s total and factor scores correlated positively with the total scores of the IRC-C/GSES (r = 0.18–0.64; all p < 0.01). The Cronbach’s alpha coefficients for the total questionnaire and individual factors ranged from 0.73 to 0.95, retest reliability from 0.64 to 0.92, and split-half reliabilities from 0.71 to 0.94.ConclusionThe Competency Scale for Psychological Peer Counselors in Colleges of Ethnic Areas demonstrates robust reliability and validity, making it a reliable tool for future screening of psychological peer counselors in ethnic-area colleges and universities.